1) is the first answer and 2) is the last answer
Answer:
y=400/300x
Step-by-step explanation:
Hello there!
n - 5 ≤ 5n - 1
Solve for n
Let's start by subtracting 5n from both sides
n - 5 - 5n ≤ 5n - 5n - 1
n - 5 - 5n ≤ -1
We need to transfer -5 on the other side, we can do that by adding 5 on both sides
n - 5 - 5n + 5 ≤ -1 + 5
n - 5n ≤ -4
-4n ≤ -4
Finally divide both sides by -4
-4n/-4 ≤ -4/-4
n ≥ -1 (This is the answer)!
Do you know why I changed the sign?
A lot of students failed to remember that rules, which is:
When you are solving an inequality, if you divide both sides by a negative sign, you MUST change the symbol as well. If it was this <, it will change to this >. Got it? Cool!
I hope the steps are clear to understand. If you have questions, feel free to let me know...
As always, I am here to help!
Answer:
Hence the expression
.
Step-by-step explanation:
- The given expression is (x+8)(x+3).
- We have to multiply the given expression.
- Multiply the (x+8) by 3 , multiply the (x+8) by x then add like terms.
![$$\begin{array}{r}x+8 \\\underline {\times \quad x+3} \\3 x+24 \\\underline {x^{2}+8 x+24} \\x^{2}+11 x+24\end{array}$$](https://tex.z-dn.net/?f=%24%24%5Cbegin%7Barray%7D%7Br%7Dx%2B8%20%5C%5C%5Cunderline%20%7B%5Ctimes%20%5Cquad%20x%2B3%7D%20%5C%5C3%20x%2B24%20%5C%5C%5Cunderline%20%7Bx%5E%7B2%7D%2B8%20x%2B24%7D%20%5C%5Cx%5E%7B2%7D%2B11%20x%2B24%5Cend%7Barray%7D%24%24)
Answer:
Step-by-step explanation:
= (x^2 + h^2 - 2xh) + (y^2 + k^2 - 2yk) As, (a-b)^2 = a^2 + b^2 - 2ab
= x^2 + h^2 - 2xh + y^2 + k^2 - 2yk